Research on the Wear Resistance of Wear-Resistant Materials - Zhu, Hongzheng; Liu, Yin; Zhu, Jinbo; Cai, Chuanchuan (Asian Journal of Chemistry, 2013)
Test is the traditional research method of the wear resistance of wear-resistant materials, but it is complex and complicated. Now a new method, which is described clearly with a industrial example, is put forward. With the new method, the number of the jet impact force can be simulated by GAMBIT and FLUENT. The study is significant for the optimization of the characteristic of the wear-resistant materials and the structure of the device.